Silicone Oil Emulsification after Vitrectomy for Rhegmatogenous Retinal Detachment - Jian Yu; Yuan Zong; Chunhui Jiang; Haohao Zhu; Guohua Deng; Gezhi Xu (Journal of Ophthalmology)
Purpose. To investigate the characteristics of silicone oil (SO) emulsification after vitrectomy for rhegmatogenous retinal detachment and their possible correlations with clinical factors. Methods. The first 2 mL of washing out fluid after SO removal was collected, and used for the measurement of the size and number of SO droplets using a Multisizer® 3 Coulter counter (Beckman Coulter, USA). The correlations between SO droplets and clinical factors were analyzed. Results. A total of 38 patients (23 males, 15 females) who underwent primary PPV with SO injection for RRD and whose retina stayed attached for ≥3 months after SO removal were included in the study. The average number of oil droplets was 1.96 × 106 ± 3.95 × 106/mL (range 0.17 × 106 to 21.71 × 106/ml), and 80.8% (range 64.23%–99.07%) of the droplets were 1-2 μm in diameter. The total number of emulsified SO droplets was not correlated with any clinical factor (all P>0.05). When the emulsified SO droplets were divided into groups by their diameter, multiple linear regression revealed that age was negatively correlated with the numbers of 5–7-μm-diameter and 7–12-μm-diameter droplets (both P<0.05). Patients using antiglaucoma medications had more 5–7-μm-diameter and 7–12-μm-diameter droplets than those not using (all P<0.05). Conclusion. Using a Multisizer® Coulter counter, we successfully determined the number and size of SO droplets after emulsification. We found that the number of 5–12-μm-diameter droplets was higher in younger-age patients and was higher in patients using antiglaucoma eyedrops.